1993
DOI: 10.1002/etc.5620120608
|View full text |Cite
|
Sign up to set email alerts
|

Reductive dechlorination of aroclor 1242 in anaerobic sediments: Pattern, rate and concentration dependence

Abstract: Anaerobic biotransformation of polychlorinated biphenyls of Hudson River sediment microorganisms was investigated using the commercial mixture Aroclor 1242 in the laboratory at six different concentrations: 120, 300, 500, 800, 1,000, and 1,500 μg/g (on a sediment dry‐weight basis). Dechlorination was concentration dependent. No change in congener composition was found at 1,000 and 1,500 μg/g during seven months of incubation, but significant shifts were observed in sediments with concentrations below 800 μg/g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…2a). Interestingly, additional dechlorination of these same identical congeners was also noted in our earlier long-term studies of Aroclor 1242 [5] and 1254 [29]. With further incubation of the natural sediments a second phase of dechlorination ensued after 15 months, with the total chlorines per biphenyl decreasing slightly further from 2.5 to 2.4 (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…2a). Interestingly, additional dechlorination of these same identical congeners was also noted in our earlier long-term studies of Aroclor 1242 [5] and 1254 [29]. With further incubation of the natural sediments a second phase of dechlorination ensued after 15 months, with the total chlorines per biphenyl decreasing slightly further from 2.5 to 2.4 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…All sediment slurry preparation took place within an anaerobic chamber (Coy Laboratory Products, Ann Arbor, MI, USA) containing an oxygen-free atmosphere of N 2 :CO 2 :H 2 (85:5:10). We previously reported that the PCB extraction efficiency of this method is greater than 96% and does not change with length of sediment incubation [5]. The sediment slurries contained 20% (w/v) of each type of sediment on a dryweight basis.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations